What factors influence British medical students' career intentions?. (December 2014) - Ibrahim, Michael; Fanshawe, Angela; Patel, Vanash; Goswami, Karan; Chilvers, Geoffrey; Ting, Michelle; Pilavakis, Yiannis; Rao, Christopher; Athanasiou, Thanos
Abstract Aim: The aim of this study was to identify factors that influence career choice in UK medical students. Methods: Students at seven institutions were invited to rate how important various factors were on influencing their career choices and how interested they were in pursuing different specialties. The influence of interpersonal relationship networks on career choice was also evaluated. Results: 641 responses were collected. 44% (283) were male, 16% (105) were graduates and 41% (263) were final-year students. For Dermatology (p = 0.009), Paediatrics (p = 0.000), Radiology (p = 0.000), Emergency Medicine (p = 0.018) and Cardiothoracic Surgery (p = 0.000), there was a clear correlation between completing a clinical attachment and an interest in pursuing the specialty. Perceived characteristics of the speciality, individually and in clusters were considered important by specific subgroups of students, such as those interested in surgery. These students considered prestige (p = 0.0003), role models (p = 0.014), financial rewards after training (p = 0.0196) and technical challenge (p = 0.0011) as important factors. Demographics such as sex and age played a significant role in career choice. Interpersonal relationship networks do not have a significant influence on career intentions. Conclusions: This study shows that the career intentions of British medical students are influenced by their undergraduate experience and by the weight they place on different specialty-related factors.